Yayasan UMPSA Scholarship 2024: English Written Test - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2024)
26 April 2024 - It remains a dream for many students to secure funding for their studies without enduring the strain of part-time jobs or burdening their parents. Among the standard prerequisites for scholarship eligibility is proficiency in English language. This criterion ensures that applicants can effectively participate in English-medium coursework, lectures, and other academic